The Contribution of PRIM Qassim in Strengthening Muhammadiyah Ideology for Indonesian Diaspora Students in Saudi Arabia - Ghazy Ahmad Filando; Nur Farid Khoiruddin; Marsekal Rahman Hakiem; Sayyid Sayyaf; Mirza Auliaur Rahman; Muh Adam Haqiqi (Universitas Ahmad Dahlan, 2026)
This study investigates the contribution of the Pimpinan Ranting Istimewa Muhammadiyah (PRIM) Qassim in strengthening Muhammadiyah ideology for Indonesian diaspora students in Saudi Arabia. It aims to explore how ideological values are internalized, practiced, and sustained within a transnational academic and socio-religious environment. Adopting a qualitative descriptive approach with a case study design, this research was conducted at Qassim University, Saudi Arabia. Data were collected through semi-structured interviews, participant observation, and document analysis involving Indonesian students actively engaged in PRIM Qassim. Participants were selected using purposive and snowball sampling techniques. Data analysis followed an interactive thematic model comprising data reduction, data display, and analytical verification to ensure rigor and credibility. The findings demonstrate that PRIM Qassim functions as a strategic ideological agent by facilitating systematic cadre development through Islamic study circles, halaqah, scientific discussions, and value-oriented social interactions. Muhammadiyah ideology is not transmitted as a rigid doctrine but is lived as a dynamic praxis that integrates faith, intellectual engagement, and social responsibility. This process significantly contributes to the formation of progressive Islamic identity, ideological resilience, and moral integrity among Indonesian students in the diaspora context. This study offers original empirical evidence on the micro-level dynamics of Muhammadiyah ideological transmission in a transnational setting. It enriches scholarly discourse on Islamic movements, diaspora studies, and transnational religious education, while providing practical insights for strengthening Muhammadiyah global cadre development strategies.